Application of the oxycodone templated molecular imprinted polymer in adsorption of the drug from human blood plasma as the real biological environment; a joint experimental and density functional theory study - Khanlari, Maryam; Daraei, Bahram; Torkian, Leila; Shekarchi, Maryam; Manafi, Mohammad Reza (Frontiers in Chemistry, 2023)
In this project, we have synthesized and used a molecular imprinted polymer (MIP) for adsorption of oxycodone residue from the biological samples. Indeed, this study aims to develop a suitable method for determination of oxycodone drug residue in the human plasma using the common analysis methods. Therefore, the MIP was used for the solid phase extraction (MIP-SPE) approach in order to collect the oxycodone opioid and to concentrate it in the blood plasma samples. The extraction parameters such as adsorption time, pH, and the amount of sorbent in blood plasma were optimized and the capacity of loading amount (LA) for adsorbing it was determined. Moreover, a high performance liquid chromatography (HPLC)-UV detector method was validated and used for analyzing of the mentioned opioid extracted from plasma. The results showed that the limit of detection (LOD), and the limit of quantization (LOQ) for the developed MIP-SPE method were 1.24 ppb, and 3.76 ppb, respectively. Moreover, both of the MIP-, and non-imprinted polymers (NIP)-drug complexes were designed and were then optimized by the density functional theory (DFT) method. The results showed that the theoretical calculations supported the experimental data, confirming the favorability of adsorption of the drug by MIP compared to NIP.